2022
DOI: 10.1080/21645515.2022.2102354
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage among health-care workers during the COVID-19 epidemic in 2020/2021 influenza season: Evidence from a web-based survey in northwestern China

Abstract: Vaccinating health-care workers against influenza during the COVID-19 pandemic can effectively prevent and control influenza and reduce COVID-19 strain on health systems. This study was conducted to explore influenza vaccination coverage and determinants among health-care workers during the COVID-19 pandemic in 2020/2021 influenza season in Ningxia. This cross-sectional survey included demographic characteristics of health-care workers, influenza vaccination status, reasons for not getting vaccinated, and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This data aligns with an analysis conducted in intensive care units and nursing homes on HCWs' VC [30], which also observed a marked decrease in VC. Some studies had already indicated a certain decline in VC during the 2021/2022 season [5,24,27,[30][31][32][33][34][35], but the figures still remained similar to those obtained at the beginning of the pandemic, around 50-60%.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This data aligns with an analysis conducted in intensive care units and nursing homes on HCWs' VC [30], which also observed a marked decrease in VC. Some studies had already indicated a certain decline in VC during the 2021/2022 season [5,24,27,[30][31][32][33][34][35], but the figures still remained similar to those obtained at the beginning of the pandemic, around 50-60%.…”
Section: Discussionsupporting
confidence: 56%
“…In the literature, we can observe that some of the main reasons for rejecting vaccination are as follows: the lack of a sense of influenza risk and the belief that the flu is not a severe illness [2,27,34,[38][39][40][41], concerns about side effects [27,32,[34][35][36][37][40][41][42][43], distrust of vaccine safety [22,32,34,35,37,39], doubts about vaccine efficacy [27,32,34,35,37,39,40], considering it unnecessary [32], self-perception as a healthy population [22,27,36], and workload as a barrier to either accessing vaccination points or a lack of time [27,32,39,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, HCWs reported concerns about COVID-19 vaccine safety as the main reason for vaccine refusal. Many international surveys have depicted aspects of similar results regarding SIV and COVID-19 vaccination [ 15 , 46 , 47 , 53 , 58 , 59 , 60 , 61 ]. Studies have also demonstrated that different occupational groups may require different approaches to overcome vaccine hesitancy [ 44 ].…”
Section: Discussionmentioning
confidence: 93%